SEJARAH TEKS AL-QUR’AN: Studi atas Pemikiran John Wansbrough - Sulaiman Ibrahim (Farabi, 2017)
The history of the Qur’an is not only intended to illustrate the process of memorizing, recording, collecting Qur'an in chronological order, but more important is the placement of such material as an argument to prove the genuineness and authenticity of the Qur'an. Is there any guarantee that the verses of the Quran does not change in any process that elapsed before recorded in Mushaf Utsmani?. This statement was expressed by John Wansbrough criticize the history of the Qur'anic text. assurance of God in keterpeliharaannya, many opportunities that enable change. Initial recording of the companions of the Qur’an in the form of remembering, of course, is still questionable, because of forgetfulness possessed by humans. Thus they create a record then used as the basis for unification, there may be a doubt for reasons of simplicity existing stationery. On the basis of all the opponents of the Qur'an does not stop doubting the authenticity and originality of the Qur'an.